(untitled) (Archives of Mechanics - Test, 2010)
Stiffness constant and effective mass are two important parameters in the performance analysis of an accelerometer. Their values depend mostly on the structural design of the comb finger-type accelerometer, especially its suspension beam design. In this study, the formulation of the stiffness constant and effective mass is derived successfully from theoretical analysis. The performance of the accelerometer can be analyzed using common designs of its suspension beam. The results obtained are comparable with other published results and those obtained from the finite element (FE) analysis.